Synthesis and Hybridization Properties of Covalently Mercurated and Palladated Oligonucleotides - Ukale, Dattatraya; Maity, Sajal; Hande, Madhuri; Lönnberg, Tuomas (Synlett, 2019)
Covalent metalation of the base moieties affords a new class of modified oligonucleotides. These organometallic oligonucleotides share many properties, notably increased hybridization affinity conferred by metal-mediated base pairing, with oligonucleotides incorporating coordinative transition-metal complexes. They are, however, set apart by their ability to retain the transition-metal ion even at extreme dilution. Such stability towards dissociation would be desirable in DNA nanotechnology and necessary in therapeutic applications. Herein we describe our efforts towards preparation and characterization of covalently mercurated and palladated oligonucleotides, highlighting in particular our recent contribution on the synthesis and potential applications of oligonucleotides incorporating dimercurated artificial nucleobases.1 Introduction2 Synthesis of Covalently Mercurated and Palladated Oligonucleotides3 Hybridization Properties of Covalently Mercurated and Palladated Oligonucleotides4 Outlook
Keywords: organometallic; oligonucleotide; mercury; palladium; hybridization